Towards More Predictive, Physiological and Animal-free In Vitro Models: Advances in Cell and Tissue Culture 2020 Conference Proceedings. Issue 3 (May 2021) - Singh, Bhumika; Abdelgawad, Mohamed Essameldin; Ali, Zulfiqur; Bailey, Jarrod; Budyn, Elisa; Civita, Prospero; Clift, Martin J.D.; Connelly, John T.; Constant, Samuel; Hittinger, Marius; Kandarova, Helena; Kearns, Victoria Rosalind; et al.
Experimental systems that faithfully replicate human physiology at cellular, tissue and organ level are crucial to the development of efficacious and safe therapies with high success rates and low cost. The development of such systems is challenging and requires skills, expertise and inputs from a diverse range of experts, such as biologists, physicists, engineers, clinicians and regulatory bodies. Kirkstall Limited, a biotechnology company based in York, UK, organised the annual conference, Advances in Cell and Tissue Culture (ACTC), which brought together people having a variety of expertise and interests, to present and discuss the latest developments in the field of cell and tissue culture and in vitro modelling. The conference has also been influential in engaging animal welfare organisations in the promotion of research, collaborative projects and funding opportunities. This report describes the proceedings of the latest ACTC conference, which was held virtually on 30th September and 1st October 2020, and included sessions on in vitro models in the following areas: advanced skin and respiratory models, neurological disease, cancer research, advanced models including 3-D, fluid flow and co-cultures, diabetes and other age-related disorders, and animal-free research. The roundtable session on the second day was very interactive and drew huge interest, with intriguing discussion taking place among all participants on the theme of replacement of animal models of disease.